Optimization Design of Pumping Unit Reversing Mechanism based on Output Swing Angle Analysis - Liu Yongping Li Dawei Dong Changbin (Jixie chuandong)
Aiming at the problem that the output angle of the elliptical gear planetary gear train reversing mechanism with small beam pumping unit is small and can not meet the long stroke demand, the influencing factors of the output swing angle of the mechanism are analyzed, and the results are expressed in the transmission ratio curve of a pair of non-circular gear pairs with the graphical area. According to the analysis results, the non-circular gear pair transmission ratio curve that meets the application requirements is constructed, the section curve equation of the non-circular gear is solved, the three-dimensional model of the mechanism is established and the motion simulation is performed, and the output swing angle and the output angular velocity amplitude curve are obtained. Analysis results show that， compared with the original elliptical gear planetary gear train reversing mechanism, the swing angle of the output is increased, so that the stroke of the pumping unit can be increased.